Genetic Screening of Candida albicans Inactivation Mutants Identifies New Genes Involved in Macrophage-Fungal Cell Interactions - Godoy, Pablo; Darlington, Peter John; Whiteway, Malcolm (Frontiers in Microbiology, 2022)
Candida albicans, an important fungal pathogen of humans, displays different morphologies, such as yeast, pseudo-hyphae and hyphae, which are recognized unequally by phagocytic cells of the innate immune response. Once C. albicans cells invade host tissues, immune cells such as macrophages are attracted to the site of infection and activated to recognize, engulf and kill the pathogen. We have investigated this fungal cell-macrophage interface by using high-throughput screening of the C. albicans GRACE library to identify genes that can influence this interaction and modify the kinetics of engulfment. Compared with the wild-type strain, we identified generally faster rates of engulfment for those fungal strains with constitutive pseudo-hyphal and hyphal phenotypes, whereas yeast-form-locked strains showed a reduced and delayed recognition and internalization by macrophages. We identified a number of GRACE strains that showed normal morphological development but exhibited different recognition and engulfment kinetics by cultured macrophages and characterized two mutants that modified interactions with the murine and human-derived macrophages. One mutant inactivated an uncharacterized C. albicans open reading frame that is the ortholog of S. cerevisiae OPY1, the other inactivated CaKRE1. The modified interaction was monitored during a 4h co-culture. Early in the interaction, both opy1 and kre1 mutant strains showed reduced recognition and engulfment rates by macrophages when compared with wild-type cells. At fungal germ tube initiation, the engulfment kinetics increased for both mutants and WT cells, however the WT cells still showed a higher internalization by macrophages up to 2h of interaction. Subsequently, between 2 and 4h of the interaction, when most macrophages contain engulfed fungal cells, the engulfment kinetics increased for the opy1 mutant and further decreased for the kre1 mutant compared with Ca-WT. It appears that fungal morphology influences macrophage association with C. albicans cells and that both OPY1 and KRE1 play roles in the interaction of the fungal cells with phagocytes.